2014
DOI: 10.1097/cej.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Tea, coffee, and caffeine and early-onset basal cell carcinoma in a case–control study

Abstract: Objectives Tea and coffee are hypothesized to play a protective role in skin carcinogenesis via bioactive components, such as caffeine, yet the epidemiologic evidence is mixed. Existing data supports an inverse association with basal cell carcinoma (BCC) more so than for melanoma or squamous cell carcinoma. To understand if tea, coffee, and caffeine are related to early-onset BCC, we evaluated data from 767 non-Hispanic Whites under age 40 in a case-control study in Connecticut. Methods BCC cases (n=377) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The consumption of caffeinated coffee is more common than that of decaffeinated coffee; thus, data that demonstrate that the consumption of a special type of coffee confers an advantage are lacking, even though caffeine exerts anticancer activities, as discussed in this review. By comparing the effects of regular coffee consumption and decaffeinated coffee consumption, several clinical studies revealed that caffeinated coffee drinkers are at a lower risk of developing cancer, unlike decaffeinated coffee consumers (Ferrucci et al 2014;Giri et al 2011;Hildebrand et al 2013).…”
Section: Epidemiological Studies and Bioavailabilitymentioning
confidence: 99%
“…The consumption of caffeinated coffee is more common than that of decaffeinated coffee; thus, data that demonstrate that the consumption of a special type of coffee confers an advantage are lacking, even though caffeine exerts anticancer activities, as discussed in this review. By comparing the effects of regular coffee consumption and decaffeinated coffee consumption, several clinical studies revealed that caffeinated coffee drinkers are at a lower risk of developing cancer, unlike decaffeinated coffee consumers (Ferrucci et al 2014;Giri et al 2011;Hildebrand et al 2013).…”
Section: Epidemiological Studies and Bioavailabilitymentioning
confidence: 99%
“…However, the results for other studies found no such associations [ 12 14 ]. In contrast, several epidemiological studies have also evaluated the associations between the decaffeinated coffee and melanoma risk, but none of them found a statistically significant association [ 9 , 12 , 13 , 15 18 ]. As the results of the epidemiological studies are inconsistent, we herein systematically reviewed the epidemiological studies that have assessed the associations between the caffeinated or decaffeinated coffee intake level and the risks for MM, and further assessed their associations utilizing meta-analysis methods.…”
Section: Introductionmentioning
confidence: 99%
“…After further evaluation, a total of 74 papers describing 8 intervention studies and 66 observational studies were eligible for inclusion in the qualitative analysis. Of these, 24 studies were related to cancer ( Table 1 ), [ 17–40 ] and 50 studies to cardiometabolic diseases ( Table 2 ). [ 41–90 ]…”
Section: Methodsmentioning
confidence: 99%